BUSINESS MODEL ANALYSIS AT BAITUL MAAL WATAMWIL (BMT) COOPERATIVE OF UNIVERSITY OF MUHAMMADIYAH JAKARTA WITH THE APPROACH OF BUSINESS MODEL CANVAS (BMC) - Nuzulul Rachman Ambara (Multidisciplinary Research Studies in Social Sciences, 2025)
The purpose of this study is to examine the business model canvas from a sharia perspective, and to find out whether the business model canvas can be used in BMT UMJ. This study intends to construct and analyze the sharia-based business model canvas, to find out the business model currently used by BMT UMJ and to make a SWOT analysis of BMT UMJ. The researcher chose to use a qualitative research method to determine how to find, collect, process and analyze the research data. Theoretically, the qualitative research format is different from the quantitative research format, and the data used are primary and secondary data. The data collection methods used are observation, interviews, and documentation. The results of the study show that BMT UMJ can use the sharia-based canvas business model if it adds several additional contracts such as wadiah contract and rahn contract, increases the number of BMT UMJ employees, and increases funding by 20%.Key Words : SWOT Analysis, Business Model Canvas (BMC), BMT UMJ